Successful treatment of bilateral endogenous Fusarium solani endophthalmitis in a patient with acute lymphocytic leukaemia. Issue 1 (22nd September 2017) - Rizzello, Ilaria; Castagnetti, Fausto; Toschi, Pier Giorgio; Bertaccini, Patrizia; Primavera, Laura; Paolucci, Michela; Faccioli, Luca; Spinardi, Luca; Lewis, Russell E.; Cavo, Michele; Stanzani, Marta
Summary: Fusarium spp. are an uncommon cause of fungaemia in immunocompromised and neutropenic patients that may hematogenously disseminate to the eyes. Herein, we describe a patient with acute lymphoblastic leukaemia and a prior history of extensive corticosteroid exposure who developed disseminated Fusarium solani infection following chemotherapy despite posaconazole prophylaxis. She was successfully treated with combination liposomal amphotericin B and voriconazole, intraocular injections of voriconazole, topical amphotericin B and bilateral vitrectomy. We also review published literature describing the management of endogenous Fusarium endophthalmitis in immunocompromised hosts.